성범죄를 저지른 소아성애자의 임상적 특징 - 문지용(Ji-Yong Moon); 임경옥(Kyung-Ok Lim); 조성남(Seongnam Cho); 장소영(Soyeong Jang); 차승민(Seung-Min Cha); 한송이(Songy (Singyŏng chŏngsin ŭihak, 2021)
Objectives This study compared the demographic and clinical characteristics, including blood testosterone level and intellectual capacity, between pedophilia and other types of paraphilia. Methods The medical records of 115 subjects with paraphilia who committed sex crimes and were admitted to National Forensic Hospital from January 2009 to December 2019 were analyzed retrospectively. The subjects were divided into two groups: the pedophilia group (n=59) and other paraphilia group (n=56). The demographic and clinical parameters, including intelligence quotient and blood testosterone level, were compared between the two groups. The characteristics of the sexual offenders were compared according to the age of the victims. Results Among the 115 subjects, 54 (46.9%) were diagnosed with pedophilia. The pedophilia group showed a significantly lower level of testosterone in their blood (t=-2.409, p=0.018), and higher comorbidity of intellectual disability than the paraphilia group (χ2=6.962, p=0.008). In addition, paraphilia subjects who had sexually offended victims under 18 years of age showed a higher frequency of pedophilia (67.2%, p=0.001), and a higher frequency of intellectual disability than those with adult victims (χ2=3.893, p=0.048). Conclusion In this study, pedophilia subjects showed lower blood testosterone levels and higher comorbidity of intellectual disability than those with other types of paraphilia. Further study will be needed to prevent sexual offending based on these findings. KCI Citation Count: 1